Programa Bolsa Família no Estado do Espírito Santo : análise das transferências financeiras do governo federal para o programa e suas condicionalidades - Veiga, Alex Golffetto da (2015)
The state of Espírito Santo stands out by regional disparities. Coexist in the state dynamic and modern regions in contrast to backward or undeveloped and stagnant regions. In this context, the conditional cash transfer programs are now part of the social development agenda, with an innovative aspect for reducing and breaking the cycle of poverty between generations, compliance with conditionalities on education and health by their beneficiaries. The objective of this research is whether there is a statistically significant correlation between the volume of financial transfers received by families in the Espírito Santo municipalities from the “Programa Bolsa Família” (PBF) and the federal financial transfers to areas of education and health in these municipalities. The research was based on contemporary theories of distributive justice through theoretical contributions of John Ralws, Amartya Sen and Milton Friedman. The technique consists of a multiple linear regression analysis, based on secondary data for the period 2007 to 2014. The technique It was applied to the group of 78 municipalities as well as for the groups separated by geographic regions and population size. The results revealed that the significant direct transfers are associated, and the model applicable to a range of 78% to 82% of the variations observed by the set of variables. Financial transfers FUNDEB have a strong impact on financial transfers PBF, while financial transfers SUS contributed to low values in this impact. It can be concluded that the financial transfers received by families PBF positively influence the demand for public educational and health services, identifying greater role of the Federal Government on the promotion of education and income redistribution actions. The practical relevance of this research is in the proposed apllication of the linear correlation analysis method as a tool in the design, intervention, monitoring of public policies in the state of Espírito Santo